Impact of Supervision and Supervisor Capability on the Construction Supervision in Enrekang - Guli, Mulyadi; Halim, Paisal; Badruddin, Syamsiah; ., Hartono; A. Abdullah, Hasim; Ikhsan Setiawan, Muhammad; Saleh A, A (International Journal of Engineering and Technology, 2018)
The aim of this study is to determine the influence of supervisory mechanism and supervisor capabilities, either in group or individually on the effectiveness of physical development supervision in Enrekang District. The results showed scores for supervisory mechanism and supervisor capability were good. The result of statistical analysis shows that there is a significant influence on the supervisory mechanism and the ability of the supervisor on the effectiveness of the supervision of physical development in Enrekang District, either partially (individually) or simultaneously (together).Â